Karakteristik individu, pengetahuan perpajakan, dan sosialisasi perpajakan terhadap kepatuhan wajib pajak orang pribadi - Lasmi, Ni Wayan; Laksmi P, Kadek Wulandari; Dewi, Made Risma (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Taxes are a source of income and, until now, the backbone of state revenues. The tax contribution to state revenue is increasing every year. Taxpayers' understanding of the applicable tax provisions and regulations is necessary so that taxpayers will be more aware of fulfilling their obligations to pay taxes. The purpose of this study was to determine the effect of individual characteristics, tax knowledge, and tax socialization on individual taxpayer compliance. The data used is primary data from distributing questionnaires to individual taxpayers registered at the South Badung KPP Pratama. The method used is a quantitative descriptive analysis method using the SPSS analysis tool. The results obtained indicate that individual characteristics, knowledge of taxation, and tax socialization have a significant positive effect on individual taxpayer compliance at KPP Pratama South Badung.